THE IMPROVED METHODS AND THEIR ANALYSIS IN BARIATRIC SURGERY. (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2023)
Objective:  Analysis of bariatric surgery outcomes, risk factors, and prevention of possible complications.Materials and methods.At the multidisciplinary clinic of the Tashkent Medical Academy 120 patients underwent bariatric surgery during 2021-2023. Retro- and prospective methods were used.The results: Early and late complications were significantly reduced after the use of improved techniques.Conclusion: First of all, the use of high technologies in the implementation of LSR creates a wide opportunity to prevent its intraoperative complications. Early and late complications - metabolic acidosis, carrying out new scientific researches predicting the development of stenoses in advance and developing treatment tactics will avoid uncorrectable complications in the postoperative period.